(untitled) (Journal of Nuclear Technology in Applied Science, 2019)
This study is established to evaluate the impact of iron and steel industry in Egypt on the public and environment.The study involved five companies for iron and steel production. Forty-two raw materials samples, eight waste sampleswere collected from the selected companies as well as sixty-eight soil samples were collected inside and around the companies.The activity concentrations of 226Ra, 232Th,40K and 137Cs were determined applying Hyper-Pure Germanium (HPGe) detector. Radiological health parameters such as radium equivalent,annual gonadal equivalent dose and excess lifetime cancer risk were estimated to assess health implication of exposure to the general public and workers to the studied samples. Heavy metals (Cd, Cr, Cu, Fe, Mn, Ni, Pb, Zn, and As) were determined by ICP- OES. Contamination factor, contamination degree and pollution load index of heavy metals were estimated; in addition pollution load index (PLI) of zones was used to compare the pollution levels between the studied companies.The activity concentration of 226Ra, 232Th, 40K, and 137Cs in soil samples ranged from < 0.7 to 257.5, < 0.6 to 25.4, 3.63 to 1578, and < 0.04 to 18.6 Bqkg-1 respectively. Soil samples have hazard indices within safe limit and don’t pose a significant health hazard except some soil samples around the first company. Concentration of Cd, Cr, Cu, Fe, Mn, Ni, Pb, Zn, and As ranged from (0.038 to 57), (2.265 to 922.65), (3.97 to 774.2), (5184.3 to 99669.2), (94.2 to 17299), (4.00 to 129.5), (6.0 to 1322.7), (43.2 to 2716.1), and (0.025 to 22.3) ppm respectively. The most polluted zone is the third company showing PLI = 3.3 and the most contributed site is S50 beside the electric arc furnace as a result of its elevated concentrations of Cd, Zn, and Pb.The obtained results are used as a baseline data for monitoring possible radioactivity and heavy metals pollutions in the future around the iron and steel industry in Egypt.Some recommendation should be carried out such as Erasing contaminated soil and monitoring the accumulation of heavy metals in soil samples is very important.